Dishwashing Soap-Making Training as an Effort to Increase Family Income in Sei Kepayang Barat Village - Sitorus, Zunaida; Efendi, Elfin; Syahrani, Nadia; Bintan, Sri; Faridz, M.Rizky Al (Golden Ratio of Data in Summary, 2026)
Liquid dishwashing soap is a household necessity with promising business potential due to its high consumption rate. This community service activity aimed to provide training on liquid dishwashing soap production and marketing strategies for the residents of West Sei Kepayang Village, Sei Kepayang District. The program was carried out through outreach, demonstrations, and mentoring. The results showed that participants were able to produce high-quality liquid soap with effective cleaning power, stable foam, a pleasant fragrance, and a long shelf life. In addition, the participants acquired practical skills in simple packaging and marketing, including direct sales and social media promotion. This activity not only enhanced their technical skills but also fostered an entrepreneurial mindset within the community. Therefore, the training is expected to serve as a sustainable home-based business opportunity and contribute to increasing family income.